Evans’ Chiral Auxiliary‐Based Asymmetric Synthetic Methodology and Its Modern Extensions - Chen, Ling‐Yan; Huang, Pei‐Qiang (European journal of organic chemistry, 2024)
Although the asymmetric catalysis has made a spurt of progress, the use of chiral auxiliaries remains crucial in asymmetric synthesis due to both the reliability and versatility of the methods, and the predictability of stereochemistry of the reactions. Up to date, Evans’ chiral non‐racemic oxazolidinone‐based asymmetric synthetic methodology is still widely used in asymmetric synthesis. More importantly, the Evans asymmetric synthetic methodology turned out to be a fruitful source of inspiration for the development of related asymmetric synthetic methodologies. However, although reviews on the application of Evans’ asymmetric synthetic methodology in both organic synthesis and medicinal chemistry continually to appear in the literature, a comprehensive review dedicating to the extensions of Evans’ chiral non‐racemic oxazolidinone‐based asymmetric methodology remains elusive. In this review, we summarize the extensions of the Evans asymmetric methodology, which cover: (1) the modification of the chiral oxazolidinone auxiliaries; (2) the extension of the Evans’ asymmetric aldol reaction from Evans’ syn‐aldol to other diastereomeric aldol adducts; (3) the extension of the asymmetric reaction types; (4) the extension of chiral imide‐type substrates to N‐alkenyl, N‐allenenyl and N‐alkynyl oxazolidinones; (5) the achiral oxazolidinone‐based asymmetric catalysis; (6) the catalytic transformation of Evans’ products; and (7) the straightforward transformations of Evans’ chiral products to other classes of compounds than the chiral carboxylic acids, esters, alcohols, and Weinreb amides. In this review, the extensions of the Evans asymmetric methodology are summarized from seven aspects. It also indicates that the asymmetric methodology still stands as an indispensable tool for accessing enantiomeric natural products and medicinal agents due to the reliability, scalability, and predictability.